DEVELOPMENT OF DIGITAL LEARNING BASED INTERNATIONAL COOPERATION IN ELEMENTARY SCHOOL TEACHERS - Panji Adam Agus Putra; Yuda Dharma Putra; Maman Surahman; Heru Pratikno; M Zidan Al Insyani; Intan Nurapriliani; Nurbani Syifa (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Collaboration programs with international organizations develop all aspects, especially in the field of education that the university has carried out. The activity was educating the elementary school teachers because it has a significant component in the educational process. The university education system has a substantial role in preparing competitive human resources. This study result findings in the form of language and cultural differences is the main issues in the implementation of the international collaboration programs. The method was used group discussions between Indonesian and Thai teachers through an innovative approach to digital learning media in a more structured and in-depth way. Group discussion case studies successfully provided practical and interactive experiences to the participants. It was concluded that mutual understanding of culture between teachers and students was fundamental and needs to be considered so that learning can be done effectively and comfortably. Educators can jointly build awareness of the effectiveness of using technology in the classroom. Technology was not only used but has a significant impact on learning processes and outcomes. The implementation of this international collaboration program aims to solve the problems faced and enhance cooperation between the two countries further.